2022
DOI: 10.3390/ma15124289
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Alkali–Silica Reaction Potential in Aggregates from Iran and Australia Using Thin-Section Petrography and Expansion Testing

Abstract: The alkali–silica reaction can shorten concrete life due to expansive pressure build-up caused by reaction by-products, resulting in cracking. Understanding the role of the aggregate, as the main reactive component, is essential for understanding the underlying mechanisms of the alkali–silica reaction and thereby reducing, or even preventing, any potential damage. The present study aims to investigate the role of petrographic studies along with accelerated tests in predicting and determining the potential reac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Kazemi et al [27] investigated ASR in concrete produced from Portland cement and different aggregates such as granite, rhyodacite, limestone, and dolomite by applying ASTM C1260 and ASTM C1293 test methods followed by optical microscope, SEM, EDX, and XRD characterization methods and found that rhyodacite specimens have higher alkali-reactivity potential than granite specimens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kazemi et al [27] investigated ASR in concrete produced from Portland cement and different aggregates such as granite, rhyodacite, limestone, and dolomite by applying ASTM C1260 and ASTM C1293 test methods followed by optical microscope, SEM, EDX, and XRD characterization methods and found that rhyodacite specimens have higher alkali-reactivity potential than granite specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 12. (Na + K)/Si-ratio of mortars LC; BC; BCFA; and ASR1, ASR2, ASR3[54], and ASR4 concretes[27]; •, , ♦, samples[56] as a function of their Ca/Si ratio.…”
mentioning
confidence: 99%
“…The ASR was examined using aggregates from different countries using petrographic analysis and expansion measurements. Kazemi et al [12] 3…”
Section: Introductionmentioning
confidence: 99%
“…They interact with the silanol groups present in the silicate phases of the aggregates [1,2]. At the end of this reaction, an alkali-silica gel product is obtained, which transforms from crypto-crystalline to amorphous structure [3]. When the alkali-silica gel absorbs water, the volume of this gel increases.…”
Section: Introductionmentioning
confidence: 99%